The Simple Macroeconomics of Fiscal Austerity, Public Sector Debt and Deflation - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
This paper explores the macroeconomics of fiscal austerity and deflation in an economy with public debt. A binding budget deficit cap destabilizes the economy by turning the government budget into an automatic destabilizer. Public debt helps maintain AD in the presence of deflation because deflation increases the real value of public interest payments. That makes public debt significantly different from private debt. If the economy is subject to a binding deficit cap, deflation no longer stabilizes output. This is because increased real interest payments must be matched by spending cuts, giving rise to a negative balanced budget multiplier.
urn:nbn:de:101:1-201101312864
Keywords: E12; E60; E62; H62; 330; fiscal austerity; budget deficit cap; public debt; deflation growth theory; Haushaltskonsolidierung; Haushaltskonsolidierung; Öffentliche Schulden; Deflation; Konjunkturtheorie; Theorie